(untitled) (Vietnam Journal of Community Medicine, 2023)
Objectives: To describe the clinical and subclinical characteristics of patients with multiple myeloma. Subjects and methods: A retrospective and prospective descriptive study on 96 patients with multiple myeloma diagnosed, treated and autologous stem cell transplantation at the Ho Chi Minh City Blood Transfusion Hematology Hospital from 2018 to 2021. Results: The most common form of multiple myeloma was monoclonal IgG (62.8%), followed by IgA monoclonal increase (18.75%) and light chain (18.75%). The group of multiple myeloma patients in stage II accounted for the highest percentage (69.8%), followed by stage I (18.7%). The number of patients hospitalized in stage III accounted for the lowest rate (11.5%). The mean hemoglobin concentration was 94.1 ± 20.4 (g/l), white blood cell count (6.42 ± 2.38 G/l), platelet count (186.4 ± 75.3 G/l) l), bone marrow cell count (71.16 ± 68.7 G/l), percentage of plasma cell lineage in the marrow (35.6 ± 21.3 %). IgG (6281.0 ± 2938.6 mg/L), IgA (3521.4 ± 1405.3 mg/L), Free Kappa (1201.5 ± 1422.1), Free Lambda (2194.7 ± 2421) ,1), ß2 microglobulin (4.24 ± 6.67 mg/L). Conclusion: The most common type of multiple myeloma was monoclonal IgG. The group of patients with multiple myeloma in stage II accounted for the highest percentage.